A New Indexing Method for Cachexia - Durán-Vila, Núria; Pina, José A.; Molins, M.; Navarro, Luis (IOCV, 2022)
The utilization of nucleic acid extraction and polyacrylamide gel electrophoresis as an alternative to the Parson's Special bioassay for routine indexing of cachexia was evaluated. Three field sources of citrus viroids and three greenhouse controls were graft inoculated on Arizona Etrog citron. Inoculated citrons were periodically analyzed by nucleic acid extraction and sequential gel electrophoresis. The citrus cachexia viroid (CCaV) was detected after 3 months in all the plants tested regardless of the source. Three electrophoresis systems were also compared. The proposed method combines the desirable characteristics of citron as an excellent host for viroid replication and the sensitivity of electrophoresis and silver staining for viroid detection. The method is now routinely used in the Citrus Sanitation Program in Spain.